Diana, Juno, Venus y Vesta en la propaganda monetaria de Adriano, Antonino Pio y sus esposas - Garzón Blanco, Jose Antonio (Estudios humanísticos. Geografía, historia y arte, 1989)
This word es trying to investigate in two important aspects the imperial roman propaganda through numismatics, we refer to the concepts of goddess greaters and smallers, which was awarded the Roman emperors and members of the imperial family. Apart from the classical sources, this study of coins is the best source which fells us about these concepts; all taken from the II century A.D. from governments of Hadrian to Antonino Pio. This being the period in which more emphasis was used.Historia